Sanders II/III Calcaneus Fractures in Laborers: A Cost-Effectiveness Analysis and Call for Effectiveness Research. Issue 6 (June 2017) - Clement, R. Carter; Lang, Pamela J.; Pettett, Brett J.; Overman, Robert A.; Ostrum, Robert F.; Tennant, Joshua N.
Abstract : Objective: This study compares the cost and cost-effectiveness of treatments options for Sanders II/III displaced intra-articular calcaneus fractures (DIACFs) in laborers. Methods: Literature on Sanders type II and III fractures was reviewed to determine complication rates and utility values for each treatment option. Costs were calculated using Medicare reimbursement and implant prices from our institution. Monte Carlo simulations were used to analyze a decision tree to determine the cost and cost-effectiveness of each treatment from a societal perspective. Sensitivity analysis was performed on all variables. Results: Minimally invasive open reduction internal fixation (ORIF) (sinus tarsi approach with 4 screws alone) was least expensive ($23, 329), followed by nonoperative care ($24, 530) and traditional ORIF using extensile lateral approach ($27, 963) ( P < 0.001); this result was most sensitive to time out of work. Available cost-effectiveness data were limited, but our analysis suggests that minimally invasive ORIF is a dominant strategy, and traditional ORIF is superior to nonoperative care (incremental cost-effectiveness ratio $57, 217/quality-adjusted life year). Conclusions: Our findings suggest that minimally invasive ORIF (sinus tarsi approach) is the least expensive option for managing Sanders II/III displaced intra-articular calcaneus fractures, followed by nonoperative care. Our cost-effectiveness results favor operative management but are highly sensitive to utility values and are weakened by scarce utility data. We therefore cannot currently recommend a treatment course based on value, and our primary conclusion must be that more extensive effectiveness research (ie, health-related quality of life data, not just functional outcomes) is desperately needed to elucidate the value of treatment options in this field. Level of Evidence: Economic Level III. See Instructions for Authors for a complete description of levels of evidence.